A new giant species of Clinopodes from the Alborz Mountains, at the eastern edge of the genus range (Chilopoda: Geophilidae) - Zarei, Roghaieh; Bonato, Lucio (Zootaxa, 2022)
A new species of Clinopodes C. L. Koch, 1847, Clinopodes azadi n. sp., is described and illustrated, based on two specimens from Alborz Mountains, Iran. The new species lives in the easternmost part of the Western Palearctic range of the genus and is outstanding in comparison to all other known Clinopodes species, being the largest (surpassing 11 cm in length) and with the highest number of body segments (89–91 leg-bearing segments). C. azadi n. sp. differs from the other Clinopodes species also in the coxosternite of first maxillae (with a distinct mid-longitudinal sutural sulcus) and in the coxal pores (numerous, and sparse on the entire surface of the coxopleura).